Cybersecurity and the Future of Work in Information Technology - Boaventura, Júlia Marques; Rosa, Phelipe Romano Magalhães; Veríssimo, Rafael; de Castro, Ryan Marques; Santos, Vinícius Meireles Pereira; Soares, Liziane Santos (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
Cybersecurity is constantly evolving, driven by the growing need for specialized professionals as threats become more sophisticated. With the increasing number of mobile and distributed devices connected to the Internet of Things (IoT), vulnerabilities are more exposed. Advanced Artificial Intelligence models, like Deep Learning, are crucial for detecting ransomware, phishing, and DDoS attacks before they occur. The global shift toward remote and hybrid work, accelerated by the Covid-19 pandemic, has introduced new challenges, including securing home networks and protecting sensitive data outside corporate environments. This article highlights the importance of cybersecurity for the future of IT work, focusing on the current landscape, challenges related to IoT security, the role of Artificial Intelligence in defending against cyberattacks, the rising demand for cybersecurity professionals, and future prospects in the field.